Epistemology and economics contribution to the logical analysis of economic theory. Claudio Gutiérrez - Gutiérrez, Claudio (San José, C.R : EUCR, 1969)
Enfoque metodológico de la teoría económica
Keywords: TEORIA ECONOMICA; ECONOMIA; EPISTEMOLOGIA; METODOLOGIA